39 Genetic Associations between Feeding Behavior and Economic Interest Traits in Group-Housed Broilers. (21st September 2022) - Carvalho Alves, Anderson A; Fernandes, Arthur F A; Lopes, Fernando B; Breen, Vivian; Hawken, Rachel; Rosa, Guilherme J J M
Abstract: This study aimed to assess the genetic relationship among feeding behavior (FB), feed efficiency (FE), and production traits in broilers. A total of 44, 234, 350 feeders visit logs from 55, 400 birds allocated into 88 trials were recorded by radio-frequency identification system. The daily data were averaged per animal for FB traits, considering the entire trial period. FB traits included the number of meals (NMEAL, count/day), time spent at feeders (TSF, hours/day), average portion size (PS, g), feeding rate (FR, g/hour), feeding activity range (FAR, hours/day), number of visited stations (NVS, count/day), and number of visited feeders (NVF, count/day). The total feed intake (FI), residual feed intake (RFI), and feed conversion rate (FCR) were also considered. Further, the body weight was measured at the start (SBW) and ending (FBW) of the trial. Multi-trait animal models were fitted for estimating the (co)variance components, considering the effects of sex and contemporary group as fixed. FB traits presented moderate to high heritability (h 2 ) values, ranging from 0.26±0.02 (FAR) to 0.58±0.02 (TSF), whereas for FE and growth traits the h 2 ranged from 0.16±0.01 (FBW) to 0.27±0.02 (RFI). The traits NMEAL, NVS, NVF, and FAR presented negative genetic correlations with FI, SBW, and FBW (-0.36 to -0.13) while PS and FR were positively correlated with all FE and production traits (0.12 to 0.43). RFI only presented non-null genetic correlations with PS (0.26±0.04), FR (0.23±0.03), and NVS (-0.11±0.04). Similarly, NMEAL and NVS also presented a weak negative correlation with FCR (-0.12±0.05 and -0.17±0.05, respectively). FB traits have a sizable genetic component and, therefore, may present a fast response to selection. The results also suggest that future selection for welfare-related feeding behavior (e.g., NMEAL, NVS, and NVF) would not affect negatively FE traits, although it might result in lighter animal lines in the long term.